LOOP-MEDIATED ISOTHERMAL AMPLIFICATION FOR DETECTION OF C. BURNETII IN BULGARIA - M. Kunchev; V. Belcheva; E. Grigorov (Trakia Journal of Sciences)
Q fever, which is caused by Coxiella burnetii, a small, pleomorphic intracellular bacterium, is the most widespread zoonosis in the world. The chronic form of the disease can lead to disability and death. Rapid diagnosis of Q fever is needed in order that effective treatment can be initiated. The conventional retrospective diagnosis of Q fever, based on serology, is useless for the treatment of afflicted patients. Thus, molecular methods have been created to close the diagnostic gap between the onset of the disease and the presence of specific antibodies in serum. A polymerase chain reaction is a suitable and reliable method with high sensitivity and specificity, but it requires expensive equipment and post-amplification protocol. Loop-mediated isothermal amplification (LAMP) is an isothermal technique, conducted at constant temperature that can amplify a negligible amount of DNA to more than 109 copies within one hour, using special primers and polymerase. We have tested the sensitivity and specificity of LAMP in the detection of C. burnetii. The mean positive rate of LAMP and polymerase chain reaction in patients was 100% and 74%, respectively. LAMP reacted negatively with non-C. burnetii pathogens and non-infected blood samples. We conclude that LAMP is a sensitive and specific technique for the detection of C. burnetii and has advantages over serological methods and PCR that make it attractive for diagnosing Q fever in countries around the world.